A Descriptive Study of HR OPerations in Organizations in Greece. - Dr. Geranios Michail; Panoutsou Eleni (2017)
Introduction, Human Resources Management, Definition of Human Resources Management, the Role of Human Resources Management, the Function of the Human Resources Management, Attracting Human Resources, the Selection of Human Resources by Organizations, the Training and Development of the Human Resources, Trends and Changes in Human Resources Management, Challenges, the HRM System, Planning of Human Resources Management, Flexible Work Schedules, Evaluation of Performance, Complaint Management, Teamwork, Dissemination of Information, Job Security, the Value Proposition Model, Methodology, Data Collection Method, Research Design - Philosophy, Findings/Resuylts, Descriptive, Inferential Statistics, Conclusion, Recommendation, Personal Reflection, Questionnaires, Ethical Approval Form.